Development of a novel clinical outcome assessment: digital instrumental activities of daily livingResearch in context - Abbey Sawyer; Jamie Brannigan; Lisa Spielman; David Putrino; Adam Fry; Andy Ho Wing Chan; Andy Wu; Betts Peters; Erin Switalski; Esmee Dohle; Franly Rosario; Hugo Layard Horsfall; et al. (EBioMedicine)
Summary: Background: Digital technology is integral to activities of daily living, particularly instrumental activities of daily living (IADLs). However, tools that accommodate digital performance of IADLs are lacking. The aim of this study was to develop a novel Digital IADL Scale. Methods: The multi-stage methodology included: (i) deductive item generation via a systematic review and assignment to domains using a Delphi process, (ii) inductive item generation via a survey of individuals with lived experience (IWLE) of severe paralysis, (iii) item refinement via item rating surveys of content experts and IWLE, and (iv) focus group discussions with key opinion leaders. Findings: The systematic review identified 1250 IADL items from validated IADL measures, of which 353 met criteria. Deduplication reduced the deductive item set to 77, of which 42 remained following the Delphi process. IWLE generated 152 items, of which 132 met criteria. Deduplication reduced the inductive item set to 41. The combined item pool was reduced to 69 following the item rating surveys. Following focus group feedback, a list of nine domains, containing 37 items, and suggested response scale options are presented. Interpretation: We describe the initial development of a scale to assess functional independence within IADLs that may be completed digitally, which will be submitted to further validation. Funding: Support for this project was provided in kind by the Abilities Research Center. No formal funding was received.